EMOTIONAL PREPARATION OF CHILDREN FOR SCHOOL - Yusupova, Nargiza (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
The article examines the problem of children's emotional readiness for learning at school as one of the key components of general psychological readiness. The features of the emotional development of preschoolers, the factors influencing the formation of emotional stability, and the role of the family and educators in preparing the child for school life are analyzed.